PENGARUH PROMOSI JABATAN TERHADAP PRESTASI KERJA KARYAWAN PADA PT. BERINGIN LIFE - Ilyas Ilyas (Universitas Negeri Medan, 2020)
Abstract: Effect of Job Promotion on Employee Performance at PT. Beringin Life. This study aims to determine the effect of Job Promotion on Employee Performance at PT. Banyan Life. The method used is explanatory research with a sample of 82 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable Job Promotion obtained an average score of 3.42 with good criteria. Employee Performance Variable obtained an average score of 3.78 with good criteria. Job Promotion has a positive and significant effect on Employee Job Performance with a regression equation value of Y = 11.691 + 0.773X, and a correlation coefficient value of 0.761 or has a strong level of relationship with a determination value of 57.9%. Hypothesis testing obtained a significance of 0.000 <0.05.Keywords: Job Promotion, Employee Performance.Abstrak: Pengaruh Promosi Jabatan terhadap Prestasi Kerja Karyawan pada PT. Beringin Life. Penelitian ini bertujuan untuk mengetahui pengaruh Promosi Jabatan terhadap Prestasi Kerja Karyawan pada PT. Beringin Life. Metode yang digunakan adalah explanatory research dengan sampel sebanyak 82 responden. Teknik analisis menggunakan analisis statistik dengan pengujian regresi, korelasi, determinasi dan uji hipotesis. Hasil penelitian ini variabel Promosi Jabatan diperoleh nilai rata-rata skor sebesar 3,42 dengan kriteria baik. Variabel Prestasi Kerja Karyawan diperoleh nilai rata-rata skor sebesar 3,78 dengan kriteria baik. Promosi Jabatan berpengaruh positif dan signifikan terhadap Prestasi Kerja Karyawan dengan nilai persamaan regresi Y = 11,691 + 0,773X, dan nilai koefisien korelasi 0,761 atau memiliki tingkat hubungan yang kuat dengan nilai determinasi 57,9%. Uji hipotesis diperoleh signifikansi 0,000 < 0,05.Kata Kunci: Promosi Jabatan, Prestasi Kerja Karyawan.